Genetic deletions and high diversity of Plasmodium falciparum histidine-rich proteins 2 and 3 genes in parasite populations in Ghana - Duah-Quashie, Nancy Odurowah; Opoku-Agyeman, Philip; Bruku, Selassie; Adams, Tryphena; Tandoh, Kwesi Zandoh; Ennuson, Nana Aba; Matrevi, Sena Adzoa; Abuaku, Benjamin; Quashie, Neils Ben; Watters, Chaselynn; Wolfe, David; Quijada, Hugo Miranda; et al. (Frontiers in Epidemiology, 2022)
Rapid diagnostic tests (RDTs) are used to diagnose malaria in Ghana and other malaria endemic countries. Plasmodium falciparum histidine-rich protein 2 (PFHRP2) based RDTs are widely used, however the occurrence of deletions of the pfhrp2 gene in some parasites have resulted in false negative test results. Monoclonal antibodies of PFHRP2 cross reacts with PFHRP3 because they share structural similarities and this complements the detection of the parasites by RDT. These two genes were investigated in Ghanaian P. falciparum parasite population to detect deletions and the polymorphisms in exon 2 of the pfhrp2 and pfhrp3 genes. Parasite isolates (2540) from children ≤12 years with uncomplicated malaria from 2015 to 2020 transmission seasons were used. Both genes were amplified using nested PCR and negative results indicated the presence of the deletion of genes. Amplified genes were sequenced for the detection of the amino acid repeats. Deletions were observed in 30.7% (780/2540) and 17.2% (438/2540) of the samples for pfhrp2 and pfhrp3 respectively with increasing trends over the three time periods (χ2 - 10.305, p = 0.001). A total of 1632 amplicons were sequenced for each gene, analysis was done on 1124 and 1307 good quality sequences for pfhrp2 and pfhrp3 respectively. Pfhrp2 repeat polymorphisms were dominantly of types 2 (AHHAHHAAD) and 7 (AHHAAD) with large numbers of variants. A novel variant of type 14 (AHHANHATD) was seen for pfhrp2. For the pfhrp3 repeat types, 16 (AHHAAN), 17 (AHHDG) and 18 (AHHDD) were the dominant types observed. Variants of type 16 (AHHAAH) and (AHHASH) were also dominant. Repeat types 1, 2, 3, 4, 5, 6, 7, 8, 11, 13, 15, 16 and 19 were observed be shared by both genes. The haplotype diversity of both genes ranged between 0.872 and 1 indicating high diversity of the polymorphisms in the isolates. The implication of the findings of the frequencies of the pfhrp2 and pfhrp3 deletions as well as the variants of the main epitopes of the monoclonal antibodies for the RDT (types 2 and 7) in our isolates is an indication of decreased sensitivity of the RDTs in diagnosing malaria infections in Ghana.